Wayanad Landslide Disaster: Impact, Response, and Implications for Future Resilience - P. Azad; A. P. Muhammed Salim; K. S. Anoop Das (ZBW – Leibniz Information Centre for Economics, 2024)
This study evaluates the Wayanad landslides of 2024, examining their socio-economic and ecological impacts, the effectiveness of response and rehabilitation efforts, and implications for future resilience in Kerala. The landslides have caused substantial damage, disrupting the lives of plantation workers and their communities, resulting in material loss, economic decline, and long-term environmental degradation. While Kerala's immediate rescue and relief efforts, supported by NGOs and volunteers, have been commendable, the state faces challenges in implementing permanent rehabilitation and mitigation measures, making it crucial to provide access to suitable livelihoods and diversify local economies as part of an effective post-event response for the permanent rehabilitation of hundreds of survivors of Kerala's deadliest disaster. To enhance disaster preparedness, Kerala needs to adopt robust institutional mechanisms, update hazard maps, and improve early warning systems, all integrated into a comprehensive pre-event strategy. By learning from successful international frameworks and integrating advanced technologies, Kerala can strengthen its resilience against climate change-induced disasters.
Additional information: This work has just been completed and submitted for publication to the journal Economic & Political Weekly.
Keywords: Q54; H84; D74; R58; I31; 330; Wayand landslide disaster; impacts; state response; Preparedness; mitigation